Specific Aspects of Land Use Planning and Forecasting For Effective Supply Chain Management - Ivan Stafiychuk; Amir Kutliyarov; Damir Kutliyarov; Enric Galeev; Alfiya Lukmanova; Gulnaz Gubaydullina (International Journal of Supply Chain Management, 2019)
The paper describes specific aspects of land use planning and forecasting for effective supply chain management. Close attention is paid to the territorial planning projects having been implemented in the United States, England, Germany, the former Soviet Union and Russia. Land is characterized as an object for planning and forecasting as well as the basis for food security. There is a real need for area development planning and forecasting to provide management of agri-food supply chains. The paper reveals the nature and the relationship of territorial forecasting, planning and land use schemes to develop logistics. Russia has long experience in land reforms, land use planning and forecasting for further social and economic development of territories as well as effective management of supply chains in them.